Politeness Strategy Retention as a Mechanism of Pragmatic Equivalence in the Indonesian Translation of Macbeth - Khoirida, Aina (Universitas Jambi, Magister Program of English Education Department, 2026)
Literary drama translation requires translators to preserve not only semantic meaning but also the pragmatic construction of characterization. While previous studies have predominantly examined shifts in politeness strategies across languages, the role of strategy retention as a mechanism for preserving pragmatic equivalence has received little scholarly attention. This study investigates how retained politeness strategies function to preserve characterization in the Indonesian translation of Shakespeare’s Macbeth. Using a qualitative descriptive design, the study analyzes 92 utterances from Act 1 in which politeness super-strategies are retained from the source text to the target text. The findings demonstrate that translators systematically retain bald-on-record, positive politeness, and negative politeness strategies when these strategies encode socially significant meanings, including monarchical authority, in-group solidarity, and manipulative intimacy. Rather than reflecting a failure to adapt to the target culture, such retention functions as a deliberate mechanism for preserving pragmatic equivalence while maintaining the original characterization and dramatic tension. These findings extend current discussions of pragmatic equivalence by demonstrating that literary translation requires not only strategic adaptation but also strategic retention when interpersonal meanings are central to character construction.